Scheduling strategies to improve quality of service for heterogeneous data over resource constrained wireless mesh networks - Sheikh, Sajid Mubashir (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.